1980
DOI: 10.1002/zaac.19804620121
|View full text |Cite
|
Sign up to set email alerts
|

Hochdrucksynthesen einiger Carbonate mit überkritischem CO2

Abstract: Die Carbonate der Alkalimetalle und einer Reihe von Übergangsmetallen lassen sich darstellen durch Einwirkung von CO2 unter Drucken zwischen 600 und 4500 at bei Temperaturen zwischen 100 und 400°C auf entsprechende Salzlösungen, Hydroxide oder Oxide. Die auf diese Weise dargestellten Verbindungen MnCO3, FeCO3, CoCO3, NiCO3, ZrOCO3 · 2H2O, Th(CO3) · 0,5 H2O sowie die Alkalimetallcarbonate werden IR‐spektroskopisch und röntgenographisch charakterisiert. Die Strukturen von Rb2CO3 (1) und Cs2CO3 (2) werden mitgete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…Refinement of the crystal structure of the room temperature modification of g-Rb 2 [CO 3 ] (and isostructural g-Cs 2 [CO 3 ] confirmed the literature data. [22] The differences between the g-, b-, and a-phases for potassium, rubidium, and cesium carbonate are mainly due to the different orientations of the rigid carbonate ion: whereas in the g-modification the carbonate ions are inclined around two axes with respect to each other, they are inclined around only one axis in the b-phase because of an additional mirror plane running through the CO 3 2À ions. Therefore, no disorder model is necessary to match the powder-diffraction pattern of the b-modification.…”
Section: Resultsmentioning
confidence: 98%
“…Refinement of the crystal structure of the room temperature modification of g-Rb 2 [CO 3 ] (and isostructural g-Cs 2 [CO 3 ] confirmed the literature data. [22] The differences between the g-, b-, and a-phases for potassium, rubidium, and cesium carbonate are mainly due to the different orientations of the rigid carbonate ion: whereas in the g-modification the carbonate ions are inclined around two axes with respect to each other, they are inclined around only one axis in the b-phase because of an additional mirror plane running through the CO 3 2À ions. Therefore, no disorder model is necessary to match the powder-diffraction pattern of the b-modification.…”
Section: Resultsmentioning
confidence: 98%
“…The shortest CÁ Á ÁC distance in Tl 2 CO 3 at ambient pressure is 3.46 Å (Marchand et al, 1975), comparable with values observed in other M 2 CO 3 carbonates, viz. 3.16 Å in Li 2 CO 3 (Effenberg & Zemann, 1979) or up to 4 Å for Cs 2 CO 3 (Ehrhardt et al, 1980). In the high-pressure form of Li 2 CO 3 at 10 GPa this distance decreases to 2.57 Å (Grzechnik et al, 2003;Cancarevic et al, 2006).…”
mentioning
confidence: 92%
“…The compounds with alkali and alkaline earth metal cations are screened in terms of the type of FMs, [CO 3 ] 2− , [C 2 O 4 ] 2− , [C 2 O 6 ] 2− , 1 [C 4 O 4 ] 2− , 2 [C 4 O 4 ] 2− , and [C 6 O 6 ] 2− . Totally, 29 selected structures [25–44] are screened with the formula A n CO 3 (A=Li, Na, K, Rb, Cs, n =2; A=Mg, Ca, Sr, Ba, n =1), A n C 2 O 4 (A=NH 4 , Li, Na, K, Rb, Cs, n =2; A=Ca, Ba, n =1), A n C 2 O 6 (A=K, Rb, n =2), A n C 4 O 4 (A=NH 4 , H, Li, Na, Rb, Cs, n =2; A=Ca, Ba, n =1), and Na 2 C 6 O 6 , as listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…TheC ÀOunits are obtained from primary crystal information without structure optimization. Thepolarization anisotropy was acquired from static polarization according to the following formula: [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] are screened with the formula [2] YVO 4 ,r utile (TiO 2 ), [45] respectively. Na 2 C 6 O 6 possesses the largest birefringence in reported crystals to the best of our knowledge.…”
Section: Process Of Design and Explorationmentioning
confidence: 99%